Pda / mxene / nio composite material, preparation method and application thereof

CN117937047BActive Publication Date: 2026-10-16安徽得壹能源科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410081289.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-19
Publication Date
2026-10-16
Estimated Expiration
2044-01-19

AI Technical Summary

Technical Problem

最先研究的各种碳材料以及聚合物等非极性材料应用到锂硫电池隔膜中,然而它们与多硫化物之间的作用力较弱,只能通过范德华力约束多硫化物的穿梭

Benefits of technology

[0005] This invention aims to at least partially solve one of the technical problems in related technologies. Therefore, the object of this invention is to propose a PDA/Mxene/NiO composite material, its preparation method, and its applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117937047B_ABST
    Figure CN117937047B_ABST
Patent Text Reader

Abstract

The application discloses a PDA / Mxene / NiO composite material and a preparation method and application thereof.The PDA / Mxene / NiO composite material comprises hollow dodecahedron structure NiO, and the hollow dodecahedron structure NiO is sequentially coated with a first polydopamine layer, Ti3C2T x nanosheet and a second polydopamine layer from inside to outside.The application constructs the composite material with a hollow structure by coating PDA and Mxene on the NiO, so that the conductivity of the NiO is improved, and the hollow and porous structure of the NiO is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to battery separators, specifically to PDA / Mxene / NiO composite materials, their preparation methods, and applications. Background Technology

[0002] With the rapid development of society and the continuous upgrading of electronic products and electric vehicles, the development of economical, efficient, and green energy storage devices has become an urgent priority. As is well known, rechargeable batteries are one of the effective methods for energy storage. While lithium-ion batteries have been commercially applied, their inherent limitations restrict their storage capacity and energy density. Furthermore, the electrode capacity of traditional materials in lithium-ion batteries is approaching its limit (300Wh·kg). -1 ~350Wh·Kg -1 This prevents further improvements in the performance of lithium-ion batteries.

[0003] Research has found that solid elemental sulfur is stable and abundant in nature, possessing excellent characteristics such as low cost and environmental friendliness, and has great potential value in the manufacture of green batteries. Lithium-sulfur (Li-S) batteries, using lithium metal as the anode and elemental sulfur as the cathode active material, are a novel type of rechargeable secondary battery. This secondary battery has a high theoretical specific capacity (1675 mAh·g). -1 ) and theoretical energy density (2600Wh·Kg) -1 However, lithium-sulfur batteries still have some problems, such as: poor conductivity of solid sulfur and low kinetic rate during cycling; volume changes of sulfur species during electrode reactions, which damage the material structure, causing active material to detach from the aluminum foil, resulting in irreversible capacity decay and poor cycle performance; and the existence of a "shuttle effect" in polysulfides, where solid-phase S8 molecules are transformed into soluble lithium polysulfide intermediates Li2S during solid-liquid conversion. x (4≤X≤8). As charging and discharging proceed, these soluble lithium polysulfides shuttle back and forth between the two electrodes, causing irreversible losses, such as severe battery self-discharge, capacity reduction, and decreased coulombic efficiency.

[0004] To address the aforementioned problems in lithium-sulfur batteries, researchers have made improvements to various aspects, including the cathode and electrolyte. Membrane modification has proven to be one of the effective ways to improve the problems in lithium-sulfur batteries in recent years. Ordinary lithium-sulfur battery membranes are made of polypropylene (PP) or polyethylene (PE), which have relatively large pore sizes and are non-polar, making it difficult to suppress the diffusion of polysulfides. Adding a coating material to the membrane surface can significantly alleviate the "shuttle effect" of polysulfides. Initially, various carbon materials and polymers were used in lithium-sulfur battery membranes; however, the interaction between these materials and polysulfides is weak, and the shuttle effect can only be constrained through van der Waals forces. Summary of the Invention

[0005] This invention aims to at least partially solve one of the technical problems in related technologies. Therefore, the object of this invention is to propose a PDA / Mxene / NiO composite material, its preparation method, and its applications.

[0006] In a first aspect, the present invention provides a PDA / Mxene / NiO composite material, comprising a hollow dodecahedral NiO, wherein the hollow dodecahedral NiO is sequentially coated from the inside out with a first polydopamine layer, a Ti3C2T layer, and a Ti3C2T layer. x Nanosheets and a second polydopamine layer.

[0007] The PDA / Mxene / NiO composite material of the present invention constructs a hollow composite material by coating NiO with PDA and Mxene, which improves the conductivity of NiO while maintaining the hollow and porous structure of NiO.

[0008] A second aspect of the present invention provides a method for preparing a PDA / Mxene / NiO composite material, comprising the following steps:

[0009] (1) Provides NiO with a hollow dodecahedral structure and Ti3C2T with a porous structure x Nanosheets;

[0010] (2) The hollow dodecahedral NiO was dispersed in Tris buffer, and dopamine hydrochloride was added to carry out the first reaction to coat the hollow dodecahedral NiO with polydopamine; then Ti3C2T was added. x The porous nanosheets undergo a second reaction to coat Ti3C2T onto polydopamine. x Porous nanosheets; finally, dopamine hydrochloride is added for a third reaction, so that polydopamine coats the whole, resulting in a PDA / Mxene / NiO composite material.

[0011] In a second aspect of the invention, polydopamine (PDA) and Ti3C2T are coated onto a hollow dodecahedral NiO structure in a stepwise manner. x Porous nanosheets (MXene) were used to obtain a PDA / MXene / NiO composite material, in which the NiO inside retained its hollow structure. PDA coating stabilized the hollow dodecahedral structure of NiO, preventing the hollow structure in the composite material from collapsing during charge and discharge, thereby improving the cycle stability of the lithium-sulfur battery. Furthermore, coating with PDA and MXene improved the conductivity of NiO.

[0012] According to an embodiment of the present invention, the first reaction includes stirring at room temperature for 1 to 2 hours. This results in the coating of polydopamine onto a hollow dodecahedral NiO structure.

[0013] According to an embodiment of the present invention, the second reaction includes stirring at room temperature for 0.5 h to 1 h. This results in the coating of polydopamine with MXene.

[0014] According to an embodiment of the present invention, the third reaction includes stirring at room temperature for 15 to 20 hours. This further forms polydopamine for overall coating.

[0015] According to an embodiment of the present invention, at least one of the following conditions is satisfied in step (2):

[0016] The pH of the Tris buffer solution is 7.5–9.

[0017] According to an embodiment of the present invention, in step (2), during the first reaction, the mass ratio of the hollow dodecahedral NiO to the dopamine hydrochloride is 1:(0.05~0.5). This controls the amount of polydopamine coating on the NiO surface to improve conductivity while better maintaining the hollow structure of NiO.

[0018] According to an embodiment of the present invention, the hollow dodecahedral NiO and the Ti3C2T x The mass ratio of porous nanosheets is 1:(0.5–2). Therefore, Ti3C2T is controlled on the product obtained from the first reaction. x The increased coating of porous nanosheets further improves the conductivity of NiO while saving raw materials.

[0019] According to an embodiment of the present invention, the mass ratio of the hollow dodecahedral NiO in step (2) to the dopamine hydrochloride added in the third reaction is 1:(0.05~0.5). This further stabilizes the overall structure of the composite material to prevent Ti3C2T x Porous nanosheets detach.

[0020] A third aspect of the invention provides the application of the PDA / Mxene / NiO composite material described in the second aspect as a separator material in lithium-sulfur batteries.

[0021] In a third aspect, the hollow PDA / Mxene / NiO composite material is applied to the separator of a lithium-sulfur battery. On the one hand, NiO can form Ni-S bonds with polysulfides, thereby inhibiting the diffusion of polysulfides and reducing sulfur loss. On the other hand, it can physically restrict the shuttle movement of polysulfides. Compared with one-dimensional / two-dimensional materials, the hollow structure can accommodate more sulfur species, and the sufficient space gap can effectively alleviate the volume expansion during charging and discharging. Furthermore, the composite material has more active sites, which adsorb polysulfides through chemical action and inhibit the shuttle movement of polysulfides, enabling the lithium-sulfur battery to exhibit excellent electrochemical performance and stable cycle performance.

[0022] According to an embodiment of the present invention, the application includes the following operations:

[0023] The PDA / Mxene / NiO composite material, conductive agent, and binder are mixed and ground, and N-methylpyrrolidone is added to adjust the viscosity to obtain a diaphragm slurry. The diaphragm slurry is then coated onto a diaphragm, dried, and punched to obtain a diaphragm sheet.

[0024] Carbon nanotubes or kochin black are mixed with sulfur, then mixed with conductive carbon black and binder, ground and mixed with NMP solvent and stirred evenly. The positive electrode slurry is then coated on aluminum foil, dried and punched to obtain the positive electrode sheet.

[0025] A lithium-sulfur battery is assembled using the positive electrode as the positive electrode, the separator as the separator, and the lithium sheet as the negative electrode, together with the electrolyte.

[0026] According to embodiments of the present invention, the mass ratio of the PDA / Mxene / NiO composite material, the conductive agent, and the binder is 9:1:0, 8:1:1, 9:0.5:0.5, or 7:2:1.

[0027] According to an embodiment of the present invention, the diaphragm is one of a polypropylene porous membrane, a polyethylene porous membrane, or a polyimide diaphragm.

[0028] According to an embodiment of the present invention, the coating thickness of the diaphragm slurry on the diaphragm is 5 μm to 20 μm.

[0029] The areal density of the positive electrode slurry coated on the aluminum foil is 1.0 mg / cm³. 2 ~1.2mg / cm 2 .

[0030] According to an embodiment of the present invention, the solvent of the electrolyte includes 1,3-dioxolane and ethylene glycol dimethyl ether, and the solute includes LiTFSI and LiNO3.

[0031] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0032] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:

[0033] Figure 1 This is a cross-sectional view of the lithium-sulfur battery separator in Example 1. Detailed Implementation

[0034] The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the invention, and should not be construed as limiting the invention.

[0035] Research on lithium-sulfur batteries has revealed a strong interaction between polar transition metals and polysulfides, effectively mitigating the "shuttle effect" of polysulfides. Therefore, polar transition metal compounds have been continuously developed. Studies have shown that transition metal oxides exhibit good adsorption properties for polysulfides, leading to the development of various transition metal oxides such as MnO2, TiO2, and Co3O4. NiO has attracted widespread attention due to its strong chemical interaction with polysulfides. NiO can form Ni-S bonds with polysulfides, thereby inhibiting polysulfide diffusion and reducing sulfur loss. However, NiO is an intrinsic semiconductor with poor conductivity. The simplest way to improve the conductivity of NiO is to physically mix it with carbon materials. However, this method easily leads to uneven mixing, and the hollow, porous structure of pure NiO is easily damaged during charge-discharge processes or other environments, severely affecting battery performance. Maintaining the hollow, porous structure of NiO while improving its conductivity is a challenging task.

[0036] In a first aspect, the present invention provides a PDA / Mxene / NiO composite material, comprising a hollow dodecahedral NiO, wherein the hollow dodecahedral NiO is sequentially coated from the inside out with a first polydopamine layer, a Ti3C2T layer, and a Ti3C2T layer. x Nanosheets and a second polydopamine layer.

[0037] In a first aspect, a hollow composite material is constructed by encapsulating PDA and Mxene, which improves the conductivity of NiO while maintaining the hollow and porous structure of NiO.

[0038] A second aspect of the present invention provides a method for preparing a PDA / Mxene / NiO composite material, comprising the following steps:

[0039] (1) Provides NiO with a hollow dodecahedral structure and Ti3C2T with a porous structure x Nanosheets;

[0040] (2) The hollow dodecahedral NiO was dispersed in Tris buffer, and dopamine hydrochloride was added to carry out the first reaction to coat the hollow dodecahedral NiO with polydopamine; then Ti3C2T was added. x The porous nanosheets undergo a second reaction to coat Ti3C2T onto polydopamine. x Porous nanosheets; finally, dopamine hydrochloride is added for a third reaction, so that polydopamine coats the whole, resulting in a PDA / Mxene / NiO composite material.

[0041] In a second aspect of the invention, polydopamine (PDA) and Ti3C2T are coated onto a hollow dodecahedral NiO structure in a stepwise manner. x Porous nanosheets (MXene) were used to obtain a PDA / MXene / NiO composite material, in which the NiO inside retained its hollow structure. PDA coating stabilized the hollow dodecahedral structure of NiO, preventing the hollow structure in the composite material from collapsing during charge and discharge, thereby improving the cycle stability of the lithium-sulfur battery. Furthermore, coating with PDA and MXene improved the conductivity of NiO.

[0042] In some embodiments, the first reaction includes stirring at room temperature for 1 to 2 hours, for example, 1 hour, 2 hours, etc. This results in the coating of polydopamine onto a hollow dodecahedral NiO structure.

[0043] In some embodiments, the second reaction includes stirring at room temperature for 0.5 h to 1 h, for example, 0.5 h, 1 h, etc. This results in the coating of MXene onto the polydopamine.

[0044] In some embodiments, the third reaction includes stirring at room temperature for 15 to 20 hours, for example, 15 hours, 18 hours, 20 hours, etc. This further forms polydopamine for overall coating.

[0045] In some embodiments, at least one of the following conditions is met in step (2):

[0046] The pH of the Tris buffer solution is 7.5–9, for example, 7.5, 8, 9, etc.

[0047] In some embodiments, during step (2), the mass ratio of the hollow dodecahedral NiO to the dopamine hydrochloride in the first reaction is 1:(0.05-0.5), for example, 1:0.05, 1:0.1, 1:0.25, 1:0.4, 1:0.5, etc. This controls the amount of polydopamine coating on the NiO surface to improve conductivity while better maintaining the hollow structure of NiO.

[0048] In some embodiments, the hollow dodecahedral NiO and the Ti3C2T x The mass ratio of porous nanosheets is 1:(0.5–2), for example, 1:0.5, 1:1, 1:1.5, 1:2, etc. Thus, Ti3C2T is controlled on the product obtained from the first reaction. x The increased coating of porous nanosheets further improves the conductivity of NiO while saving raw materials.

[0049] In some embodiments, the mass ratio of the hollow dodecahedral NiO in step (2) to the dopamine hydrochloride added in the third reaction is 1:(0.05-0.5), for example, 1:0.05, 1:0.1, 1:0.25, 1:0.4, 1:0.5, etc. This further stabilizes the overall structure of the composite material to prevent Ti3C2T x Porous nanosheets detach.

[0050] A third aspect of the invention provides the application of the PDA / Mxene / NiO composite material described in the second aspect as a separator material in lithium-sulfur batteries.

[0051] In a third aspect, the hollow PDA / Mxene / NiO composite material is applied to the separator of a lithium-sulfur battery. On the one hand, NiO can form Ni-S bonds with polysulfides, thereby inhibiting the diffusion of polysulfides and reducing sulfur loss. On the other hand, it can physically restrict the shuttle movement of polysulfides. Compared with one-dimensional / two-dimensional materials, the hollow structure can accommodate more sulfur species, and the sufficient space gap can effectively alleviate the volume expansion during charging and discharging. Furthermore, the composite material has more active sites, which adsorb polysulfides through chemical action and inhibit the shuttle movement of polysulfides, enabling the lithium-sulfur battery to exhibit excellent electrochemical performance and stable cycle performance.

[0052] In some embodiments, the application includes the following operations:

[0053] The PDA / Mxene / NiO composite material, conductive agent, and binder are mixed and ground, and N-methylpyrrolidone is added to adjust the viscosity to obtain a diaphragm slurry. The diaphragm slurry is then coated onto a diaphragm, dried, and punched to obtain a diaphragm sheet.

[0054] Carbon nanotubes or kochin black are mixed with sulfur, then mixed with conductive carbon black and binder, ground and mixed with NMP solvent and stirred evenly. The positive electrode slurry is then coated on aluminum foil, dried and punched to obtain the positive electrode sheet.

[0055] A lithium-sulfur battery is assembled using the positive electrode as the positive electrode, the separator as the separator, and the lithium sheet as the negative electrode, together with the electrolyte.

[0056] In some embodiments, the mass ratio of the PDA / Mxene / NiO composite material, the conductive agent, and the binder is 9:1:0, 8:1:1, 9:0.5:0.5, or 7:2:1.

[0057] In some embodiments, the diaphragm is one of a polypropylene porous membrane, a polyethylene porous membrane, or a polyimide diaphragm.

[0058] In some embodiments, the coating thickness of the diaphragm slurry on the diaphragm is 5 μm to 20 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, etc.

[0059] In some embodiments, the areal density of the positive electrode slurry coated on the aluminum foil is 1.0 mg / cm³. 2 ~1.2mg / cm 2 For example, 1.0 mg / cm 2 1.1 mg / cm 2 1.2 mg / cm 2 wait.

[0060] In some embodiments, the solvent of the electrolyte includes 1,3-dioxolane and ethylene glycol dimethyl ether, and the solute includes LiTFSI and LiNO3. As an example, the electrolyte is 1.0 mol / L LiTFSI + 0.2 mol / L LiNO3 dissolved in 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (1:1, V / V).

[0061] The present invention will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present invention in any way.

[0062] Example 1

[0063] S1: 1.2 g Ni(COOH)₂·4H₂O and 3.0 g polyvinylpyrrolidone (PVP) were dissolved in 180 mL of ethanol. After sonication for 30 min, the solution was heated and stirred in an oil bath at 95 °C for 8 h. After the reaction was stopped, the solution was cooled to room temperature. The solid product was then centrifuged, washed, and dried in a vacuum drying oven at 60 °C for 10 h. Finally, the dried product was calcined in a muffle furnace at a rate of 3 °C / min to 350 °C and held at 350 °C for 2 h. After calcination, NiO with a hollow dodecahedral structure was obtained.

[0064] S2: 2g LiF and 40mL hydrochloric acid (9M) were stirred until homogeneous, and the resulting solution was used as the etchant for Ti3AlC2 powder. Then, 2g Ti3AlC2 powder was slowly added to the etchant. The resulting mixture was stirred at 35℃ for 30h, then washed with deionized water and centrifuged at 3500rpm for 15min. This centrifugation and washing process was repeated several times until pH > 5. Finally, the solution was ultrasonically washed in deionized water for 1h and centrifuged at 3500rpm for 5min, and the Ti3C2T was collected. x Nanosheets.

[0065] S3: Add 100mg Ti3C2T x Nanosheets were mixed with 0.1 mL of 30 wt% H₂O₂ for 40 min, followed by the addition of 10 mL of dilute hydrochloric acid (3 M) to etch away the TiO₂ produced during the reaction. Finally, the solution was centrifuged and washed multiple times until the pH reached ≥ 6, yielding Ti₃C₂T nanosheets with pore sizes ranging from 25 nm to 30 nm. x Porous nanosheets.

[0066] S4: Disperse 0.3g NiO ultrasonically in 20mL Tris buffer (pH≈8.5), add 60mg dopamine hydrochloride while stirring, and continue stirring at room temperature for 1.5h to carry out the reaction. Then add 0.6g Ti3C2T x Porous nanosheets were reacted by stirring at room temperature for 30 min, and then 60 mg of dopamine hydrochloride was added. The mixture was stirred at room temperature for 15 h to obtain a PDA / Mxene / NiO(PMN) composite material.

[0067] S5: Preparation of lithium-sulfur battery separator:

[0068] The PMN composite material, conductive agent, and PVDF were mixed in a mass ratio of 8:1:1 and ground for 30 minutes. Then, N-methylpyrrolidone was added, stirred, and the viscosity was adjusted to obtain a slurry coating. The slurry coating was then coated on the surface of a polypropylene (PP) porous membrane and dried at 60°C for 12 hours to obtain a lithium-sulfur battery separator.

[0069] S6: Assembling lithium-sulfur batteries:

[0070] CNT / S, conductive carbon black, and PVDF were mixed in a mass ratio of 7:2:1 and ground for 30 minutes. Then, N-methylpyrrolidone was added to adjust the viscosity of the slurry. The slurry was then coated onto aluminum foil with a scraper and dried in a vacuum drying oven at 60°C for 10 hours. Finally, the dried aluminum positive electrode was cut into circular positive electrode sheets with a diameter of 12 mm.

[0071] The electrolyte was 1.0 M LiTFSI + 0.2 M LiNO3 dissolved in 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (1:1, V / V).

[0072] The negative electrode is a lithium sheet.

[0073] The positive electrode, negative electrode, separator, and electrolyte are assembled in sequence to form a lithium-sulfur battery.

[0074] The lithium-sulfur battery separator of Example 1 was subjected to SEM testing to obtain... Figure 1 The image shows a cross-sectional view of the PDA / Mxene / NiO membrane under a scanning electron microscope, revealing that the coating thickness on the membrane is approximately 10 μm.

[0075] Example 2

[0076] In this embodiment, S1, S2, and S3 are the same as in Example 1, except for S4, which involves ultrasonically dispersing 0.6g NiO in 40mL Tris buffer (pH≈8.5), then adding 120mg dopamine hydrochloride while stirring, continuing stirring for 1.5h, and finally adding 0.6g Ti3C2T. x After stirring the porous nanosheets for 30 minutes, 60 mg of dopamine hydrochloride was added to obtain a PDA / Mxene / NiO(PMN) composite material.

[0077] Example 3

[0078] In this embodiment, S1, S2, and S3 are the same as in Example 1, except for S4, which involves ultrasonically dispersing 0.6g NiO in 40mL Tris buffer (pH≈8.5), then adding 120mg dopamine hydrochloride while stirring, continuing stirring for 1.5h, and finally adding 0.3g Ti3C2T. x After stirring the porous nanosheets for 30 minutes, 30 mg of dopamine hydrochloride was added to obtain the PDA / Mxene / NiO(PMN) composite material.

[0079] Example 4

[0080] In this embodiment, S1, S2, S3, and S4 are the same as in embodiment 1, except for S5, in which the mass ratio of PMN composite material, conductive agent, and PVDF is 7:2:1.

[0081] Example 5

[0082] In this embodiment, S1, S2, S3, and S4 are the same as in embodiment 1, except for S5, in which the mass ratio of PMN composite material, conductive agent, and PVDF is 9:0.5:0.5.

[0083] Example 6

[0084] In this embodiment, S1, S2, S3, and S4 are the same as in embodiment 1, except for S5, in which the mass ratio of PMN composite material to PVDF is 9:1.

[0085] Example 7

[0086] In this embodiment, S1, S2, S3, S4, and S5 are the same as in embodiment 1. The difference is in S6, except that the positive electrode is made of KB / S, conductive carbon black, and PVDF mixed in a mass ratio of 7:2:1. All other aspects are the same as in embodiment 1.

[0087] Comparative Example 1

[0088] The only difference in this comparative example is that the membrane coating of the lithium-sulfur battery separator does not contain PDA, i.e., S5 does not contain PDA. Otherwise, it is the same as Example 1.

[0089] Comparative Example 2

[0090] The only difference in this comparative example is that the membrane coating of the lithium-sulfur battery separator does not contain Mxene, i.e., S5 does not contain Mxene. Otherwise, it is the same as Example 1.

[0091] Comparative Example 3

[0092] In this comparative example, a polypropylene (PP) porous membrane was used directly as a lithium-sulfur battery separator, and the assembly method of the lithium-sulfur battery separator was the same as in Example 1.

[0093] Test case

[0094] The lithium-sulfur batteries prepared in the examples and comparative examples were subjected to the following tests. The specific test results are shown in Table 1 below:

[0095] Test method: The prepared lithium-sulfur battery was cycled at 0.5C at room temperature for 50, 100 and 300 cycles. The capacity retention rate was calculated. The specific formula (I) is: Capacity retention rate = (specific capacity after cycling / initial specific capacity) × 100% (I).

[0096] Table 1

[0097]

[0098] As shown in Table 1, the lithium-sulfur battery in Example 1 has an initial specific capacity of 1065 mAh·g at 0.5C. -1 After 300 cycles, the capacity retention rate was 93%, and its initial specific capacity and capacity retention rate were both higher than those of Examples 2 and 3, indicating that Ti3C2T x The porous nanosheets improve the conductivity of NiO, and the higher NiO content leads to more collapse of the composite material structure, resulting in a greater capacity decay rate of lithium-sulfur batteries.

[0099] The initial specific capacity in Example 1 is lower than that in Example 4, possibly because the conductive agent content in Example 4 is higher, and the conductivity of the composite material is higher than that of the composite material in Example 1, with little difference in capacity retention. The capacity retention rate in Example 1 is higher than that in Example 5 because the PVDF content in Example 5 is reduced. This may be because the reduction of binder reduces the adhesion of the composite material to the blank separator, causing the composite material to fall off the separator during lithium-sulfur battery cycling.

[0100] The initial specific capacity in Example 1 is higher than that in Example 6, possibly because Example 6 lacks a conductive agent. The capacity retention rate is slightly lower than that in Example 6 because the absence of the powdered conductive agent in the example results in slightly greater adhesion of the composite material to the membrane.

[0101] The initial specific capacity in Example 1 is higher than that in Example 7 because the conductivity of the negative electrode material CNT in Example 1 is greater than that of KB in Example 7, since CNT can form a conductive network.

[0102] In Example 1, the initial specific capacity and capacity retention were both higher than those of Comparative Examples 1-2, indicating that Ti3C2T x Hollow nanosheets improve the conductivity of NiO, and PDA stabilizes the structural stability of the hollow composite material. In Example 1, the initial specific capacity and capacity retention rate are higher than those in Comparative Example 3, indicating that the PDA / Mxene / NiO separator can effectively block the shuttle of polysulfides, increase the utilization rate of sulfur, and thus improve the cycle and stability performance of lithium-sulfur batteries.

[0103] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0104] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A PDA / MXene / NiO composite material, characterized in that, The NiO includes a hollow dodecahedral structure, wherein the hollow dodecahedral NiO is sequentially coated from the inside out with a first polydopamine layer, a Ti3C2T layer, and a Ti3C2T layer. x Nanosheets and a second polydopamine layer.

2. A method for preparing a PDA / MXene / NiO composite material, characterized in that, Includes the following steps: (1) Provides NiO with a hollow dodecahedral structure and Ti3C2T with a porous structure x Nanosheets; (2) The hollow dodecahedral NiO was dispersed in Tris buffer, and dopamine hydrochloride was added to carry out the first reaction to coat polydopamine on the hollow dodecahedral NiO; then Ti3C2T was added. x The nanosheets undergo a second reaction to coat Ti3C2T onto polydopamine. x Nanosheets; finally, dopamine hydrochloride is added for a third reaction, so that polydopamine coats the whole, resulting in a PDA / MXene / NiO composite material.

3. The method for preparing the PDA / MXene / NiO composite material according to claim 2, characterized in that, The first reaction includes stirring the reaction at room temperature for 1 to 2 hours.

4. The method for preparing the PDA / MXene / NiO composite material according to claim 2, characterized in that, The second reaction involves stirring the reaction at room temperature for 0.5 h to 1 h.

5. The method for preparing the PDA / MXene / NiO composite material according to claim 2, characterized in that, The third reaction involves stirring the reaction at room temperature for 15 to 20 hours.

6. The method for preparing the PDA / MXene / NiO composite material according to claim 2, characterized in that, The pH of the Tris buffer solution mentioned in step (2) is 7.5~9.

7. The method for preparing the PDA / MXene / NiO composite material according to claim 2, characterized in that, In step (2), during the first reaction, the mass ratio of the hollow dodecahedral NiO to the dopamine hydrochloride is 1:(0.05~0.5).

8. The method for preparing the PDA / MXene / NiO composite material according to claim 7, characterized in that, In step (2), the hollow dodecahedral NiO and the Ti3C2T x The mass ratio of the nanosheets is 1:(0.5~2).

9. The method for preparing the PDA / MXene / NiO composite material according to claim 2, characterized in that, In step (2), the mass ratio of the hollow dodecahedral NiO to the dopamine hydrochloride added in the third reaction is 1:(0.05~0.5).

10. The application of the composite material according to claim 1 or the composite material prepared by any one of claims 2 to 9, characterized in that, Includes the following operations: The PDA / MXene / NiO composite material, conductive agent, and binder are mixed and ground, and N-methylpyrrolidone is added to adjust the viscosity to obtain a diaphragm slurry. The diaphragm slurry is then coated onto a diaphragm, dried, and punched to obtain a diaphragm sheet. Carbon nanotubes or Ketjen black are mixed with sulfur, then mixed and ground with conductive carbon black and binder. NMP solvent is added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is then coated on aluminum foil, dried, and punched to obtain a positive electrode sheet. A lithium-sulfur battery is assembled using the positive electrode as the positive electrode, the separator as the separator, and the lithium sheet as the negative electrode, together with the electrolyte.

11. The application of the composite material according to claim 10, characterized in that, When manufacturing the diaphragm sheet, the mass ratio of the PDA / MXene / NiO composite material, conductive agent, and binder is 8:1:1, 9:0.5:0.5, or 7:2:

1.

12. The application of the composite material according to claim 10, characterized in that, The diaphragm is one of polypropylene porous membrane, polyethylene porous membrane, or polyimide diaphragm.

13. The application of the composite material according to claim 10, characterized in that, The coating thickness of the diaphragm slurry on the diaphragm is 5 μm to 20 μm; The areal density of the positive electrode slurry coated on the aluminum foil is 1.0 mg / cm³. 2 ~1.2 mg / cm 2 .

14. The application of the composite material according to any one of claims 10 to 13, characterized in that, The electrolyte contains 1,3-dioxolane and ethylene glycol dimethyl ether as solvents, and LiTFSI and LiNO3 as solutes.

Citation Information

Patent Citations

  • Multifunctional diaphragm of lithium-sulfur battery and preparation method of multifunctional diaphragm

    CN112768840A

  • Lithium-sulfur battery separation film having composite coating layer including polydopamine, manufacturing method therefor, and lithium-sulfur battery comprising same

    US20180198156A1